Ana María Cano González, María Victoria Conde Sáiz, José Luis García Arias y Francisco García González, Gramática bable. Ediciones Naranco, Madrid, 1976; 111 pp. - Cristina González (Nueva Revista de Filología Hispánica, 1978)
Se reseñó el libro: Gramática bable.